Exploring The Potency of Microalgae-Based Biofertilizer and Its Impact on Oil Palm Seedlings Growth - Indiani Sani; Yudistira Wahyu Kurnia; Hana Christine Sinthya; Richard Anthony; Elizabeth Caroline Situmorang; Condro Utomo; Tony Liwang (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Indonesia is a major producer of palm oil. Consequently, the use of chemical fertilizers has become more extensive. Microalgae represent a potential alternative for enhancing and protecting crops based on their cell elements. This study applies dry biomass or liquid culture formulation of the green microalgae Haematococcus pluvialis to the rhizosphere of oil palm pre-nursery as a biofertilizer. Soil application of microalgae biomass of 0.5 g/l (MA) or liquid culture of 10% (v/v) (BCMA) is carried out to assess its effects on 4-months-old oil palm at the nursery stage. The compatibility test between microalgae and bio fungicide agents in agricultural practices, Trichoderma spp., is also tested on both microalgae formulations. The result shows that both microalgae biomass and liquid culture, alone or combined with Trichoderma spp., give a better growth performance to the oil palm. The application of MA and BCMA result in a maximum increment of plant height, leaves count, and chlorophyll content. Furthermore, the application of BCMA gives better oil palm growth performance, which may probably be influenced by the accessibility of nutrients for microalgae growth. The study reveals that soil application of microalgae as biofertilizers can improve oil palm growth performance.